Experimental Study of Polarized Radar Scattering from the Tree Canopy at the Ka-Band - Chiung-Shen Ku; Pao-Chi Chang; Yang-Lang Chang (International Journal of Antennas and Propagation)
In this study, experimental measurements were carried out to estimate the polarized backscattering coefficient at the Ka-band through deciduous and coniferous trees. By utilizing a ground-based scatterometer, the returned signal was obtained in three polarized states at an incident angle ranging from 30 to 80 degrees. The scattering coefficients were estimated from the radar equation for the distributed target under narrow beam approximation. Radiometric calibration was conducted using a metal sphere, and a set of corner reflectors was used as the calibration target to ensure measurement accuracy. Both frequency and angular response of backscattering coefficients with three polarizations were analyzed for the cases of deciduous (banyan) and coniferous (pine) trees. The results indicated that the dynamic range for HV polarization is higher than that of HH and VV polarizations for both banyan and pine trees. Comparatively, the dynamic range for the pine tree is larger than that of the banyan tree.